SCRUTINIZING KEY ELEMENTS OF GREEN LITERATURE ON THE CHILDREN’S BOOK TATA KATA: KUMPULAN CERITA ANAK COMPOSED BY YOUNG WRITERS OF THE TIN ISLAND - Sigalingging, Bob Morison; Wulansari, Dini (Lire Journal (Journal of Linguistics and Literature), 2024)
Bangka is well-known as the Tin Island. Tin mining in Bangka, both on land and at sea, actually causes environmental damage. This has been a serious issue for a long time, impacting Bangkanese lives from children to adults, in addition to air pollution. That is why the purpose of highlighting the topic is to explore the elements of green literature organized in the children's book Tata Kata: Kumpulan Cerita Anak, written by several young Bangka writers. Published in 2020, it consists of ten short stories for children at age 10–12, and one of the provided themes is environment. Interestingly, the concept of ecocriticism is present within the object itself. The study employed a descriptive-qualitative method to formulate the answers to the problem. The data were obtained through observation and in-depth interviews with the authors. The data analysis technique from Miles and Huberman (2014) played a vital role to process the data set in order to acquire profound information. The findings classified the key elements of green literature in the children's book Tata Kata: Kumpulan Cerita Anak into three categories: (a) environmental citizenship, (b) care ethics, and (c) ecoliteracy. The authors fully support the existence of these elements, as they aim to raise awareness and persuade Bangkanese children to protect and care for the environment in light of the massive emerging damage. Furthermore, the young writers implicitly criticized the nature of Bangka, which is currently endangered. It means that Bangkanese children are expected to be environmental heroes/heroines in the next few years.